Benign thyroid nodules treatment using percutaneous laser ablation (PLA) and radiofrequency ablation (RFA). (3rd April 2017) - Mauri, Giovanni; Cova, Luca; Monaco, Cristian Giuseppe; Sconfienza, Luca Maria; Corbetta, Sabrina; Benedini, Stefano; Ambrogi, Federico; Milani, Valentina; Baroli, Alberto; Ierace, Tiziana; Solbiati, Luigi
Abstract: Purpose: To evaluate the reduction over time of benign thyroid nodules treated using percutaneous laser ablation (PLA) and radiofrequency ablation (RFA) by the same equipe. Materials and methods: Ninety patients (age 55.6 ± 14.1 years) underwent ablation for benign thyroid nodule causing compression/aesthetic dissatisfaction from 2011. Fifty-nine (age 55.8 ± 14.1 years) underwent RFA and 31 (age 55.2 ± 14.2 years) PLA, ultrasound guided. Technical success, complications, duration of ablation and treatment, energy deployed, volumetric percentage reduction at 1, 6 and 12 months were derived. A regression model for longitudinal measurements was used with random intercept and random slope. Values are expressed as mean ± standard deviation or N (%). Results: Technical success was always obtained. No major complications occurred. Mean ablation time was 30.1 ± 13.8 vs. 13.9 ± 5.9 min ( p < .0001) and mean energy deployment was 5422.3 ± 2484.5 J vs. 34 662.7 ± 15 812.3 J in PLA vs. RFA group. Mean volume reduced from 20.3 ± 16.4 ml to 13.17 ± 10.74 ml (42% ± 17% reduction) at 1st month, 8.7 ± 7.4 ml (60% ± 15% reduction) at 6th month and 7.1 ± 7.7 ml (70%% ± 16% reduction) at 12th month, in PLA group, and from 32.7 ± 19.5 ml to 17.2 ± 12.9 ml (51%±15% reduction) at 1st month, 12.8 ± 9.6 ml (64 ± 14% reduction) at 6th month and 9.9 ± 9.2 ml (74% ± 14% reduction) at 12th month in RFA group. No difference in time course of the relative volume reduction between the two techniques was found. Conclusions: RFA and PLA are similarly feasible, safe and effective in treating benign thyroid nodules when performed by the same equipe. RFA is faster than PLA but require significantly higher energy.